28 GHz metal cavity‐backed twin arc slot antenna for high efficiency and thermal management. Issue 11 (29th May 2020) - Kim, Hyunjin; Nam, Sangwook
Abstract: This article presents a metal cavity‐backed antenna array with high gain and high radiation efficiency. The proposed antenna can be used for the purpose of thermal management. A 28 GHz linear polarized antenna is implemented on a low cost substrate with an aluminum structure that functions as a heat sink. Each antenna element is connected to integrated circuits with a stripline embedded in the printed circuit board. Each element is fed by a slot‐coupled feeding structure and radiated through twin arc slots fabricated in circular metal cavity. The simulated antenna efficiency is over 80% including feeding structures. The simulated and measured radiation patterns show 17.2 dBi of peak gain. From the thermal simulation, temperature reduction can be expected.